Evaluation of Long-term Outcomes and Prediction of Failure Rate of Endoscopic Third Ventriculostomy in Less Than 2 Years Children - Hasanreza Mohammadi; Masoud Sadat; Hamidreza Khayat Kashani (International Clinical Neuroscience Journal, 2020)
Background: The study carried out to assess long-term outcomes of endoscopic third ventriculostomy (ETV) on less than two years of hydrocephalous children and to determine prognostic factors of ETV success in this population. Methods: our study was a retrospective cohort study carried out on 40 hydrocephalus children who underwent ETV surgery. Clinical data retrieved from patient’s medical records, and we did an active follow-up. We used Kaplan-Meier and life-table approaches to assess 6 months success rate of ETV. We also used multiple cox regression to determine prognostic factors associated with success. Moreover, the ROC curve analysis was used to assess how ETV success score (ETVSS) can predict the possibility of ETV failure. Results: The mean age of patients at surgery time was 7.8 (±7.8) months, and 60% were male. The mean failure time of ETV was 4.5 months, and the most common etiology was aqueduct (27.0%). According to our finding age at surgery time (hazard ratio [HR]=2.2, 95% CI=1.1, 3.4) and birth age (HR=4.4, 95% CI 1.1, 17.2) were the main factors associated with ETV failure. We also observed, statistically lower HR for patients with aqueduct etiology (HR=0.1, 95% CI=0.01, 0.9). Moreover, the area under the ROC curve was estimated at 76.1, illustrating partial validity to predict ETV failure in the study population. Conclusion: According to our findings, ETV could suggest treating Hydrocephaly in young kids with particular attention on over 6-month patients and those who were mature at birth. However, more studies are required to confirm our findings.